Feminist Refiguring of La Malinche in Sandra Cisneros Never Marry A Mexican - Sutanto, Dian Natalia (LLT Journal: A Journal on Language and Language Teaching, 2015)
La Malinche, the mistress of Spanish conquistador Hern Cort, has evolved from a historical figure into Mexican national myth that connotes all the negative aspects of womans sexuality in Mexican and Mexican-American Culture. Sandra Cisneros in her Never Marry A Mexican reinterpretsLa Malinchein a more positive light and points out how women sexuality can be the site for women empowerment.By drawing on insights from feminist theories on motherhood, marriage, and incest taboo, this study identifies the way Cisneros revises the negative image of La Malinche as a dupe, passive and submissive mistress. This study identifies that Cisneros has created a strong protagonist character named Clemencia, who exerts her subjectivity and claims for her sexual agency totransgress patriarchal construction of woman passive sexuality, imposition of maternal identity as asexual mother and taboo on incestuous relationship. Cisneross La Malinche is no longer depicted as the victim duped by the patriarchy, but as the survivor who is able to preserve her sense of herself in the dominating patriarchal world.